Characterization and leaching toxicities of mercury in flue gas desulfurization gypsum from coal-fired power plants in China. (1st August 2016) - Hao, Ying; Wu, Simiao; Pan, Yun; Li, Qiu; Zhou, Jizhi; Xu, Yuebu; Qian, Guanren
Highlights: Hg pollutant characters in FGD gypsums around China were evaluated. Total content and chemical species of Hg displayed regional characters. Hg in FGD gypsums mainly distributed in strong complex F4 phase. TCLP and SPLP tests indicated low mobility of Hg in FGD gypsum. Abstract: Flue gas desulphurization (FGD) gypsum samples were collected from 70 power plants in 20 provinces in China. The total Hg concentration, chemical speciation and leaching toxicity of Hg in the samples were determined. The total Hg concentrations ranged from not detectable (ND) to 4330 μg/kg with an average of 891 μg/kg and a median of 629 μg/kg. The Hg concentrations in the FGD samples had obvious regional characteristics. Provinces in the central part of China had higher average Hg concentrations in the FGD gypsum than other provinces. Selective sequential extraction (SSE) used for chemical speciation analysis showed that water soluble and human stomach acid soluble (F1 + F2) percentages ranged from ND to 25.2% of the total Hg, and strong complex Hg (F4) was the dominant chemical species, which accounted for more than 60% of the total Hg in most samples. Moreover, the leaching Hg concentrations from Toxicity Characteristic Leaching Procedure (TCLP) and Synthetic Precipitation Leaching Procedure (SPLP) tests were all below the regulation level of leaching toxicity. The average percentage of leaching Hg from TCLP and SPLP was approximately 3% of the total Hg, indicating limited Hg mobility in FGD gypsum. The Hg potential leaching from FGD gypsum was approximately 0.65 tons per year.